Endocrine correlates of free-ranging African elephant (Loxodonta africana) treated with porcine zona pellucida vaccine - Bertschinger, H.J. (Hendrik Jan) (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2010.